1998
DOI: 10.1161/01.hyp.31.5.1166
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Injection With Antisense Oligodeoxynucleotides Against Angiotensinogen Decreases Blood Pressure in Spontaneously Hypertensive Rats

Abstract: Abstract-In the renin-angiotensin system, renin is known to cleave angiotensinogen to generate angiotensin I, which is the precursor of angiotensin II. Angiotensin II is a vasoactive peptide that plays an important role in blood pressure. On the other hand, the liver is the major organ responsible for the production of angiotensinogen in spontaneously hypertensive rats (SHR). To test the hypothesis that a reduction of angiotensinogen mRNA in the liver by antisense oligodeoxynucleotides (ODNs) may affect both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…When given iv the AGT-AS-ODN would reduce blood pressure significantly when delivered with a liposome. These studies have been confirmed by other studies independently, showing that AGT-AS-ODN reduces blood pressure for up to 7 days with a single systemic dose (6). A similar story is true for the effects of AT 1 -AS-ODN.…”
Section: Antisense Oligonucleotidessupporting
confidence: 73%
“…When given iv the AGT-AS-ODN would reduce blood pressure significantly when delivered with a liposome. These studies have been confirmed by other studies independently, showing that AGT-AS-ODN reduces blood pressure for up to 7 days with a single systemic dose (6). A similar story is true for the effects of AT 1 -AS-ODN.…”
Section: Antisense Oligonucleotidessupporting
confidence: 73%
“…Intravenous injection of antisense oligonucleotides into spontaneously hypertensive rats resulted in reduction in plasma angiotensinogen, angiotensin II, and blood pressure. 131 Antisense oligonucleotides to AGT injected into the brain of 2-kidney, 1 clip rats also reduced blood pressure substantially. 132 Mice overexpressing AGT only in the brain have elevated blood pressure.…”
Section: Autosomal Recessivementioning
confidence: 98%
“…24 Control ODN of either sense or scrambled sequences of the same length do not decrease BP. The hypertensive effect of AS treatment can be maintained with repeated administration.…”
Section: Phillips January 1999mentioning
confidence: 98%
“…Effective AS ODN have been targeted to mRNA for renin, angiotensinogen, ACE, and AT 1 -R. They have been tested in 3 different models of hypertension, including the genetic model (SHR), [21][22][23][24] a surgical model (2-kidney, 1 clip hypertension [2K1C]), 25 and an environmental stress model (coldinduced hypertension) 26 (Table 1). In every case in which we have tested the selected AS oligomers, there have been consistent biological signs of gene knockdown.…”
Section: The Antisense Oligonucleotide Approachmentioning
confidence: 99%
See 1 more Smart Citation